Rule breakers [videorecording (DVD)] - Guttentag, William; Mahboob, Elaha; Brown, Jason, 1969-; Boosheri, Nikohl; Gulamgaus, Noorin, 1997-; Afzali, Amber; Hosseinzadeh, Nina; Rowe, Sara Malal; Saraj, Mariam; Memarzia, Nasser; Ali, Waj; Binshamsī, Fahd; et al. (Angel Studios, 2025)
"In a nation where educating girls is seen as rebellion, a visionary woman dares to teach young minds to dream. When their innovation draws global attention, their success sparks hope--and opposition. As threats loom and sacrifices are made, their courage and unity ignite a movement that could forever transform the world."--